2012
DOI: 10.7124/bc.000067
|View full text |Cite
|
Sign up to set email alerts
|

RTK signaling regulator SPRY2 associates with endocytic adaptor ITSN1 in vivo

Abstract: Mitogenic signaling from RTK (receptor tyrosine kinase) is tightly linked to endocytosis that regulates the fidelity of signal transduction. Intersectin 1 (ITSN1) is an evolutionarily conserved adaptor implicated in the earliest stages of clathrin-mediated endocytosis and involved in malignant transformation when overexpressed. The aim of this study was to find proteins that could connect ITSN1 to RTK signaling. Methods. In silico prediction of interaction motifs, expression of proteins in bacterial system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We and other laboratories have demonstrated that ITSN1 through its SH3 domains forms complexes with E3-ubiquitin ligases of Cbl family [30][31][32] as well as with Sprouty 2, a negative regulator of Cbl [33,34] (Fig. We and other laboratories have demonstrated that ITSN1 through its SH3 domains forms complexes with E3-ubiquitin ligases of Cbl family [30][31][32] as well as with Sprouty 2, a negative regulator of Cbl [33,34] (Fig.…”
mentioning
confidence: 99%
“…We and other laboratories have demonstrated that ITSN1 through its SH3 domains forms complexes with E3-ubiquitin ligases of Cbl family [30][31][32] as well as with Sprouty 2, a negative regulator of Cbl [33,34] (Fig. We and other laboratories have demonstrated that ITSN1 through its SH3 domains forms complexes with E3-ubiquitin ligases of Cbl family [30][31][32] as well as with Sprouty 2, a negative regulator of Cbl [33,34] (Fig.…”
mentioning
confidence: 99%
“…ITSN1 is a multidomain and multifunctional adaptor protein which is involved in clathrin-and caveolin-dependent endocytosis [1,2], Ca 2+ -regulated exocytosis [3] and synaptic vesicles retrieval [4]. It is also implicated in cellular signaling [5][6][7] and neuron survival [8]. Abnormalities of ITSN1 expression are associated with the endocytic anomalies reported in Down syndrome brains and early stages of Alzheimer's disease as well as with neurodegeneration in Huntington's disease [9,10].…”
mentioning
confidence: 99%